PENGARUH LEVERAGE, CASH FLOW OPERATION, KEPUTUSAN INVESTASI DAN KONSERVATISME AKUNTANSI TERHADAP KUALITAS LABA (Studi Empiris Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019) - Wismawati, Wahyu (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2024)
This research is entitled The Effect of Leverage, Cash Flow Operation, Investment Decisions and Accounting Conservatism on Profit Quality in Empirical Studies in Manufacturing Companies Listed on the Indonesia Stock Exchange 2015-2019. This study aims to determine the effect of financial performance, investment decisions and accounting conservatism on earnings quality. This study uses secondary data derived from annual reports or financial statements of manufacturing companies listed on the Indonesia Stock Exchange for 2015-2019 which have been audited by an independent auditor. The population in this study is 120 with a sample size of 24 companies for 5 years. The method used in determining the number of samples is purposive sampling. Regression analysis in this study using multiple linear regression. Hypothesis testing in this study uses the t test, F test and test. The results of this study indicate that leverage and investment decisions have no effect on earnings quality. Meanwhile, cash flow operations and accounting conservatism affect earnings quality. The results of multiple linear regression analysis showed an adjusted . value of 0.056 or 5.6%. This shows that the level of the relationship between leverage, cash flow operations, investment decisions and accounting conservatism on earnings quality is 5.6% and the remaining 94.4% is explained by other variables outside the research model.